Pemahaman Maqashid Syariah (Akal) Terhadap Kinerja Lembaga Zakat Yatim Mandiri Di Surabaya - Citra Aisya Madania; Muhammad Nafik H.R (Universitas Airlangga, 2016)
The potential that zakat has in Indonesia has not been well optimized nor managed professionally, such is caused by the lack of effectiveness of zakat institutions in collecting, administrating, and distributing zakat procedures. The comprehension of maqashid sharia in regard to zakat is a determining factor in the success of zakat management. A good understanding of the maqashid sharia behind zakat will lead to better management of zakat proceedings.This research adopts a qualitative approach in an attempt to further analyze the role of understanding maqashid sharia by zakat institutions in managing zakat funds. Sources will come from 4 official of the YatimMandiri Surabaya Zakat Collector Institution. Data is collected through means of in depth interview, observation and documentation.Results showed that understanding the maqashid sharia behind zakat is a requirement in order to efficiently perform the complete zakat procedures.